The 2nd International Laayoune Forum on Biosaline Agriculture 2022
DOI: 10.3390/environsciproc2022016060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Irrigation Water Salinity Levels on Nutrients Uptake, Biochemical Content and Growth Response of Blue Panicum, Quinoa and Silage Maize

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In our experiment, the determination of mineral content indicates a high accumulation of sodium on quinoa leaves under high salinity conditions, resulting in an increase of the K/Na ratio. However, Oumasst et al (2022) observed a similar trend for sodium accumulation in the ICBA-Q5 variety under arid conditions in the south of Morocco. They found that the sodium content increased tenfold under 10 dS/m of irrigation water salinity compared to 0.9 dS/m salinity level.…”
Section: Discussionsupporting
confidence: 57%
“…In our experiment, the determination of mineral content indicates a high accumulation of sodium on quinoa leaves under high salinity conditions, resulting in an increase of the K/Na ratio. However, Oumasst et al (2022) observed a similar trend for sodium accumulation in the ICBA-Q5 variety under arid conditions in the south of Morocco. They found that the sodium content increased tenfold under 10 dS/m of irrigation water salinity compared to 0.9 dS/m salinity level.…”
Section: Discussionsupporting
confidence: 57%
“…(2021) showed that blue panicgrass yield was only reduced by 40% under high salinity with a salt concentration equal to 15000 mg.l -1 compared to control irrigated with freshwater. Adjacent to the experimental site of the present work in the Souss Massa region (central Morocco), Oumasst et al. (2021) irrigated blue panicgrass in a pot experiment with four salinity levels (1, 3, 6, and 10 dS.m -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Farrag et al (2021) showed that blue panicgrass yield was only reduced by 40% under high salinity with a salt concentration equal to 15000 mg.l -1 compared to control irrigated with freshwater. Adjacent to the experimental site of the present work in the Souss Massa region (central Morocco), Oumasst et al (2021) irrigated blue panicgrass in a pot experiment with four salinity levels (1, 3, 6, and 10 dS.m -1 ). Their obtained results revealed no significant difference between the tested salinity levels in terms of biomass yield which indicate that the salinity tolerance threshold of blue panicgrass is probably beyond 10 dS.m -1 .…”
Section: Introductionmentioning
confidence: 99%